Assessment of Development Results - Bhutan (Second Assessment) - United Nations Development Programme (United Nations, 2018)
The Independent Evaluation Office (IEO) of the United Nations Development Program (UNDP) conducts country evaluations called “Independent Country Programme Evaluations (ICPEs)”, formerly known as “Assessment of Development Results”, to capture and demonstrate evaluative evidence of UNDP’s contributions to development results at the country level, as well as the effectiveness of UNDP’s strategy in facilitating and leveraging national effort for achieving development results. This is the second ICPE for Bhutan conducted in 2017, towards the end of the current UNDP programme cycle of 2014-2018. The first ICPE for Bhutan was conducted in 2007, before the new programme cycle of 2008-2014. The current evaluation results are expected to feed into the development of the new country programme.